Variações terminológicas de enfermidades oculares no projeto atlas linguístico do Brasil : um estudo léxico-semântico dos dados sergipanos - Reis, Camila dos Santos (2020)
A linguistic atlas is an instrument that brings one of the richness of this people, your idiom, addresses linguistic variations according to special parameters, sociocultural and chronological limits, in addition to serving as a way to keep the sociolinguistic memory of a community (CARDOSO, 2010). The Projeto Atlas Línguístico do Brasil (ALiB) seeks to document, describe and interpret the reality of Brazilian Portuguese in an interface with different branches of organized knowledge (CARDOSO et al., 2014). The present work is part of the ALiB Project and realized a description and lexical-semantic analysis of the medical terminological variations of eye diseases from oral data previously collected and made available by ALiB, particularly the data from the capital of the State of Sergipe, Aracaju, as well such as those of Propriá and Estância. In addition, we observe the typologies of terminological variation (FAULSTICH, 2002) in the semantic field human body (designation ascertained by the national project) with regard to the denomination of eye diseases made by informants of two age groups, 18-30 and 50-65, of both sexes, with education up to the fourth grade and with university level (only in the city of Aracaju). At the end, we compared the results with the terminological denominations given by medical professionals specialized in the field of ophthalmology who work in the indicated locations. The methodology for organizing, classifying and analyzing data followed the pre-established and standardized standards by the ALiB National Committee (CARDOSO et al., 2014). After the analysis, we concluded that the most significant differences are present in the variable education. In addition, it was found that the specialists, despite knowing the vernacular designations, do not use them in their medical care, which makes it difficult for patients to communicate and understand the disease.